Sabores e cores - Araújo , Eliane da Silva; Lima , Eliene Xavier de; Botassim, Rosa Maria Ferreira; Corsino , Roseli da Silva; Pedrosa , Sandra Tigre Figueiredo (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf